Innate Lymphoid Cells Are Required for Endometrial Resistance to Chlamydia trachomatis Infection - Xu, Hong (Infect Immun, 2020)
In some women, sexually transmitted Chlamydia trachomatis may ascend to infect the endometrium, leading to pelvic inflammatory disease. To identify endometrial innate immune components that interact with Chlamydia, we introduced C. trachomatis into mouse endometrium via transcervical inoculation and compared the infectious yields in mice with and without immunodeficiency. Live C. trachomatis recovered from vaginal swabs or endometrial tissues peaked on day 3 and then declined in all mice with or without deficiency in adaptive immunity, indicating a critical role for innate immunity in endometrial control of C. trachomatis infection. Additional knockout of interleukin 2 receptor common gamma chain (IL-2Rγc) from adaptive immunity-deficient mice significantly compromised the endometrial innate immunity, demonstrating an important role for innate lymphoid cells (ILCs). Consistently, deficiency in IL-7 receptor alone, a common gamma chain-containing receptor required for ILC development, significantly reduced endometrial innate immunity. Furthermore, mice deficient in RORγt or T-bet became more susceptible to endometrial infection with C. trachomatis, suggesting a role for group 3-like ILCs in endometrial innate immunity. Furthermore, genetic deletion of gamma interferon (IFN-γ) but not IL-22 or antibody-mediated depletion of IFN-γ from adaptive immunity-deficient mice significantly compromised the endometrial innate immunity. Finally, depletion of NK1.1(+) cells from adaptive immunity-deficient mice both significantly reduced IFN-γ and increased C. trachomatis burden in the endometrial tissue, confirming that mouse ILCs contribute significantly to endometrial innate immunity via an IFN-γ-dependent effector mechanism. It will be worth investigating whether IFN-γ-producing ILCs also improve endometrial resistance to sexually transmitted C. trachomatis infection in women.